E-Module for Problem-Based Learning Integrating Batak Toba Culture (PBL BTC) to Improve Problem-Solving Ability - simangunsong, ita pratiwi; Napitupulu, Elvis; Lubis, Asrin; simangunsong, ika trisni (Universitas Islam Lamongan, 2024)
This research aims to analyze: 1) the validity, practicality and effectiveness of the PBL e-module based on Batak Toba Culture (PBL BTC) which was developed to increase students' problem-solving abilities at SMP Negeri 1 Simanindo; 2) increasing students' problem-solving abilities through the developed e-module. This research is using the ADDIE. From the tested of class IX 2 was obtained: 1) the PBL BTC e-module have the criteria of being valid, effective, and practical; 2) Increased problem-solving abilities using the PBL BTC e-module as seen from the N-gain value is 0.506, it is in the